2018
DOI: 10.1073/pnas.1811158115
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative conformational profiling of kinase inhibitors reveals origins of selectivity for Aurora kinase activation states

Abstract: SignificanceMany drugs trigger changes to the structure of their target receptor upon binding. These conformational effects are thought to be an essential part of molecular recognition but have proven challenging to quantify. Using a high-throughput method for tracking structural changes in a protein kinase in solution, we discovered that many clinically important cancer drugs trigger substantial structural changes to their target protein kinase Aurora A, and that these effects systematically account for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 70 publications
(104 reference statements)
3
55
0
Order By: Relevance
“…Likewise, activation loop dynamics have been suggested by simulations of the Fyn tyrosine kinase domain (31). However, to date, only Aurora A kinase has been found to undergo activation loop motions in its phosphorylated form (32)(33)(34)(35). Here, time-resolved Förster resonance energy transfer and single-molecule fluorescence spectroscopic measurements show interconversion of the phosphorylated activation loop between active and inactive conformations.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Likewise, activation loop dynamics have been suggested by simulations of the Fyn tyrosine kinase domain (31). However, to date, only Aurora A kinase has been found to undergo activation loop motions in its phosphorylated form (32)(33)(34)(35). Here, time-resolved Förster resonance energy transfer and single-molecule fluorescence spectroscopic measurements show interconversion of the phosphorylated activation loop between active and inactive conformations.…”
Section: Discussionmentioning
confidence: 73%
“…Here, time-resolved Förster resonance energy transfer and single-molecule fluorescence spectroscopic measurements show interconversion of the phosphorylated activation loop between active and inactive conformations. These are coupled with exchange between DFG-in and DFG-out conformations and can be shifted by Type II inhibitors (34,35). The characteristics of ERK2 differ from those of Aurora A in that dynamic motions of the activation loop coupled with global exchange in the active site involve movements distinct from DFG backbone rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Since we have found that these treatments do not affect endogenous AURKA levels, nor AURKA-Venus levels in intact cells, we assumed that the reduced AURKA levels seen in IF reflected loss of AURKA in the fixation step, that could be a consequence of reduced interaction with the mitotic spindle. Indeed, MLN8237 and TPX2 may compete with each other for AURKA binding 50 (see Discussion). We measured pole-pole distances in this experiment and found them reduced by PROTAC-D treatment.…”
Section: Resultsmentioning
confidence: 94%
“…Given the complex conformational and spatial regulation of AURKA 15,17,56 we tested for conformationspecific targeting of the kinase using different versions of AURKA-Venus. The conformational dynamics of AURKA are strongly constrained through interaction with TPX2 50,57,58 , which favours the so-called 'DFG-In' active confirmation and it has been suggested that different functional pools possess distinct conformational properties that will modulate interactions with inhibitors 50 . In this study, alisertib/MLN8237 was shown to be a 'Type 1' inhibitor that promotes the inactive DFG-Out state, and TPX2 to oppose DFG-Out inducers, exhibiting negative cooperativity on binding with MLN8237 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The low energetic barrier allows Vertex-11e to trap the active conformation of the activation loop, and SCH772984 to disrupt it. (35,36). Here, crystal structures of the unphosphorylated ERK2 double mutant revealed that Type II inhibitors bound to a DFG-out conformer.…”
Section: Dfg-in State Unlike What Is Observed In Structures Of Kinasmentioning
confidence: 85%